Practical guideline on obesity care in patients with gastrointestinal and liver diseases – Joint ESPEN/UEG guideline - KANİ, HALUK TARIK (My University, 2023)
Background: Patients with chronic gastrointestinal disease such as inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), celiac disease, gastroesophageal reflux disease (GERD), pancreatitis, and chronic liver disease (CLD) often suffer from obesity because of coincidence (IBD, IBS, celiac disease) or related pathophysiology (GERD, pancreatitis and CLD). It is unclear if such patients need a particular diagnostic and treatment that differs from the needs of lean gastrointestinal patients. The present guideline addresses this question according to current knowledge and evidence. Objective: The present practical guideline is intended for clinicians and practitioners in general medicine, gastroenterology, surgery and other obesity management, including dietitians and focuses on obesity care in patients with chronic gastrointestinal diseases. Methods: The present practical guideline is the shortened version of a previously published scientific guideline developed according to the standard operating procedure for ESPEN guidelines. The content has been re-structured and transformed into flow-charts that allow a quick navigation through the text. Results: In 100 recommendations (3× A, 33× B, 24 × 0, 40× GPP, all with a consensus grade of 90% or more) care of gastrointestinal patients with obesity – including sarcopenic obesity – is addressed in a multidisciplinary way. A particular emphasis is on CLD, especially metabolic associated liver disease, since such diseases are closely related to obesity, whereas liver cirrhosis is rather associated with sarcopenic obesity. A special chapter is dedicated to obesity care in patients undergoing bariatric surgery. The guideline focuses on adults, not on children, for whom data are scarce. Whether some of the recommendations apply to children must be left to the judgment of the experienced pediatrician. Conclusion: The present practical guideline offers in a condensed way evidence-based advice how to care for patients with chronic gastrointestinal diseases and concomitant obesity, an increasingly frequent constellation in clinical practice.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Yoğun Bakım; Beslenme ve Dietetik; Tarımsal Bilimler; Ziraat; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Intensive Care; Nutrition and Dietetics; Agricultural Sciences; Agriculture; Health Sciences; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Tarım Bilimleri; Klinik Tıp; BESLENME VE DİYETETİK; YOĞUN BAKIM; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); AGRICULTURAL SCIENCES; CLINICAL MEDICINE; NUTRITION & DIETETICS; CRITICAL CARE MEDICINE; Beslenme ve Diyetetik; Yoğun Bakım Tıbbı; Critical Care and Intensive Care Medicine; Gastroesophageal reflux disease; Inflammatory bowel disease; Irritable bowel syndrome, celiac disease; Obesity; Pancreatitis; Sarcopenic obesity; Obesity; Sarcopenic obesity; Inflammatory bowel disease; Irritable bowel syndrome; celiac disease; Gastroesophageal reflux disease; Pancreatitis